2014
DOI: 10.1159/000363506
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Nine Programs of Topological Predictions and Their Application to Integral Membrane Channel and Carrier Proteins

Abstract: We evaluated topological predictions for nine different programs, HMMTOP, TMHMM, SVMTOP, DAS, SOSUI, TOPCONS, PHOBIUS, MEMSAT-SVM (hereinafter referred to as MEMSAT), and SPOCTOPUS. These programs were first evaluated using four large topologically well-defined families of secondary transporters, and the three best programs were further evaluated using topologically more diverse families of channels and carriers. In the initial studies, the order of accuracy was: SPOCTOPUS > MEMSAT > HMMTOP > TOPCONS > PHOBIUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 105 publications
(135 reference statements)
0
12
0
Order By: Relevance
“…However, G130V is present in TM5, which was validated by all 5 of the programs. Recently, Reddy et al reported that different topology prediction programs are suitable for different families of proteins (37). Therefore, lack of prediction of TM7 to TM9 by some programs does not invalidate the presence of these regions in our model.…”
Section: Discussionmentioning
confidence: 96%
“…However, G130V is present in TM5, which was validated by all 5 of the programs. Recently, Reddy et al reported that different topology prediction programs are suitable for different families of proteins (37). Therefore, lack of prediction of TM7 to TM9 by some programs does not invalidate the presence of these regions in our model.…”
Section: Discussionmentioning
confidence: 96%
“…To estimate if differences in the amino acid sequences of Ssu1p transporters were associated with protein topology, transmembrane domains were predicted using SPOCTOPUS (39). SPOCTOPUS is a method for the combined prediction of signal peptides and membrane protein topology suitable for whole-genome annotation, which has shown the highest accuracy prediction compared to similar methods (40).…”
Section: Methodsmentioning
confidence: 99%
“…Though the WHAT program uses the HMMTOP program to highlight regions where predicted TMSs could be, this program sometimes predicts incorrectly, and it is ultimately up to the user to judge the actual TMS numbers (Reddy et al. ). An arbitrary criterion for a TMS would be a hydrophobic peak with a value of greater than 1 (Zhai and Saier ).…”
Section: Methodsmentioning
confidence: 99%